Electrochemically driven, cobalt–carbon bond-mediated direct intramolecular cyclic and acyclic perfluoroalkylation of (hetero)arenes using X(CF2)4X. Issue 42 (30th June 2020) - Cui, Luxia; Ono, Toshikazu; Hossain, Md. Jakir; Hisaeda, Yoshio
Abstract : A proof-of-concept for synthetically challenging cyclic and acyclic perfluoroalkylation of (hetero)arenes driven by the valence change of a cobalt catalyst with X(CF2 )4 X is demonstrated. Abstract : A proof-of-concept for the one-step, synthetically challenging cyclic and acyclic perfluoroalkylation of (hetero)arenes driven by the valence change of a vitamin B12 derivative as a cobalt catalyst in the presence of fluoroalkylating reagents (X(CF2 )4 X) is presented. The consecutive formation of cobalt–carbon bonds and generation of fluoroalkyl radicals by homolysis are the key steps for the reaction to proceed.